2010
DOI: 10.1007/s10552-010-9557-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-OH vitamin D levels and risk of developing prostate cancer in older men

Abstract: ObjectiveMultiple studies have shown clear evidence of vitamin D’s anti-tumor effects on prostate cancer cells in laboratory experiments, but the evidence has not been consistent in humans. We sought to examine the association between vitamin D and prostate cancer risk in a cohort of older men.MethodsWe conducted a prospective case-cohort study nested within the multicenter Osteoporotic Fractures in Men (MrOS) study. Baseline serum 25-OH vitamin D was measured in a randomly selected sub-cohort of 1,433 men ≥65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 41 publications
1
31
0
1
Order By: Relevance
“…For example, the paper by Barnett et al [1] found no link in their recent study between prediagnostic serum 25-hydroxyvitamin D [25(OH)D] and prostate cancer incidence in older men during a mean 5.3-year followup period [1]. This finding agrees with those of other recent reviews [2][3][4].…”
supporting
confidence: 67%
See 2 more Smart Citations
“…For example, the paper by Barnett et al [1] found no link in their recent study between prediagnostic serum 25-hydroxyvitamin D [25(OH)D] and prostate cancer incidence in older men during a mean 5.3-year followup period [1]. This finding agrees with those of other recent reviews [2][3][4].…”
supporting
confidence: 67%
“…There is also good evidence that vitamin D improves survival for those diagnosed with prostate cancer (Refs. 34 and 35 in [1]). Thus, vitamin D appears to be important in reducing the risk of prostate cancer over many years, so measuring 25(OH)D levels shortly before diagnosis of prostate cancer may not provide an accurate indication of the overall effect of vitamin D on prostate cancer risk.…”
Section: Sirmentioning
confidence: 96%
See 1 more Smart Citation
“…In most prediagnostic Nordic studies, an inverse association is found between 25(OH)D 3 levels and PC (Ahonen et al 2000). In contrast, several prediagnostic studies in the United States do not find this association (Travis et al 2009, Barnett et al 2010. Then again, in the Nordic studies almost half of the subjects were vitamin D 3 deficient compared with 20% in the US studies (Ahn et al 2008).…”
Section: Human Studies Vdr Cyp27b1 and Cyp24a1 Expressions In Cancermentioning
confidence: 96%
“…This finding led to several epidemiologic observations linking subnormal vitamin D levels to increased risk of breast (Garland, Garland et al 1990), colorectal (Jenab, Buenode-Mesquita et al 2010) and prostate cancers (Barnett, Nielson et al 2010). Giovannucci et al performed a large prospective observational cohort study composed of 51,529 U.S. male healthcare providers and illustrated that low levels 25(OH) D 3 (<25nmol/L) were associated with increased cancer incidence and mortality in men.…”
Section: Vitamin D and Solid Tumorsmentioning
confidence: 97%